Inflammatory bowel disease therapeutics: a bibliometric analysis of tofacitinib research in ulcerative colitis - Zhou, Jianping; Xi, Yuting; Zhang, Yaping; Zhang, Rui; Fu, Hao; Zhou, Ce (Frontiers in Pharmacology, 2025)
BackgroundUlcerative colitis (UC) is a chronic inflammatory bowel disease affecting millions worldwide. Tofacitinib, an inhibitor of Janus kinase (JAK), has shown considerable potential as an effective treatment option for individuals suffering from moderate to severe UC, aiming to mitigate the risk of colectomy, hospitalization, and disease exacerbation.MethodsWe conducted a comprehensive literature review from 2012 to 2024 to assess the study landscape of Tofacitinib in UC. Employing the Web of Science Core Collection database (WOSCC) and the bibliometric tool CiteSpace, we performed an bibliometric analysis to delineate disciplinary evolution and identify research hotspots within the UC Tofacitinib domain.ResultsOur analysis extracted 406 UC Tofacitinib-related articles from WOSCC, indicating a growing body of literature. The United States and Europe are at the forefront of research maturity, with a significant contribution to the field. Here we show that multidisciplinary research is burgeoning, which is crucial for the advancement of UC Tofacitinib studies. We identified 13 highly cited documents and 10 co-cited documents, highlighting Tofacitinib’s prominence as a small molecule agent. Keyword analysis revealed that the intestinal barrier, clinical response, remission rate, and safety are the central themes of current research.ConclusionBy applying bibliometrics, citation analysis, and knowledge mapping, this study provides a snapshot of the current state and trajectory of Tofacitinib research in UC. We have elucidated the knowledge lineage in this field, offering insights that can inform both ongoing and future research endeavors. Our findings underscore the importance of multidisciplinary collaboration in advancing UC therapeutic strategies.